Dissociation of Endogenous Pain Inhibition Due to Conditioned Pain Modulation and Placebo in Male Athletes Versus Nonathletes - Geisler, Maria; Herbsleb, Marco; Bär, Karl-Jürgen; Weiss, Thomas (Frontiers in Psychology, 2020)
Animals and humans are able to inhibit pain by activating their endogenous pain inhibition system. It has been shown that endurance athletes possess higher pain tolerance threshold and a greater conditioned pain modulation (CPM) effect than non-athletes suggesting a better endogenous pain inhibition. Besides CPM, placebo is another prominent paradigm testing endogenous pain inhibition. However, it has not been investigated yet, whether placebo and CPM share the same mechanisms of pain inhibition. If so, then endurance athletes should also show a greater placebo effect than non-athletes. Here we investigated 16 male endurance athletes and 17 male non-athletes in well-established placebo and CPM paradigms to assess whether the mechanisms of CPM and placebo are the same. We found a significantly greater CPM effect in athletes than in non-athletes. In contrast, we could only find a significant placebo effect in non-athletes. Furthermore, we found a strong positive association between CPM effect and exercise-induced hypoalgesia, and negative associations between placebo effect and heart rate variability, and between placebo effect and interoceptive awareness. Together, our results demonstrate a dissociation of endogenous pain inhibition of CPM and placebo effect between endurance athletes and non-athletes, suggesting that both effects do not rely on the same mechanisms.